Enrichment of transgene integrations by transient CRISPR activation of a silent reporter gene - Nanna S. Mikkelsen; Sabina S. Hernandez; Trine I. Jensen; Jessica L. Schneller; Rasmus O. Bak (Molecular Therapy: Methods & Clinical Development, 2023)
CRISPR-Cas-mediated site-specific integration of transgenes by homology-directed repair (HDR) is challenging, especially in primary cells, where inferior editing efficiency may impede the development of gene- and cellular therapies. Various strategies for enrichment of cells with transgene integrations have been developed, but most strategies either generate unwanted genomic scars or rely on permanent integration and expression of a reporter gene used for selection. However, stable expression of a reporter gene may perturb cell homeostasis and function. Here we develop a broadly applicable and versatile enrichment strategy by harnessing the capability of CRISPR activation (CRISPRa) to transiently induce expression of a therapeutically relevant reporter gene used for immunomagnetic enrichment. This strategy is readily adaptable to primary human T cells and CD34+ hematopoietic stem and progenitor cells (HSPCs), where enrichment of 1.8- to 3.3-fold and 3.2- to 3.6-fold was achieved, respectively. Furthermore, chimeric antigen receptor (CAR) T cells were enriched 2.5-fold and demonstrated improved cytotoxicity over non-enriched CAR T cells. Analysis of HDR integrations showed a proportion of cells harboring deletions of the transgene cassette arising either from impartial HDR or truncated adeno-associated virus (AAV) vector genomes. Nonetheless, this novel enrichment strategy expands the possibility to enrich for transgene integrations in research settings and in gene and cellular therapies.